Chimeric antigen receptor modified T cell therapy in B cell non‐Hodgkin lymphomas. (24th January 2019) - Levin, Adam; Shah, Nirav N.
Abstract : Chimeric antigen receptor modified T (CAR‐T) cell therapy against the CD19 antigen has revolutionized the therapeutic landscape for patients with relapsed, refractory B cell non‐Hodgkin lymphoma (NHL). Currently, there are two FDA approved products (axicabtagene ciloleucel and tisagenlecleucel) for B cell NHL, with several other constructs under clinical investigation. This review will focus on the clinical outcomes, toxicity profile, and differences among candidate CD19 CAR‐T cell products for major subtypes of B cell NHL including diffuse large B cell lymphoma, follicular lymphoma, and mantle cell lymphoma. Lastly, we will describe novel CAR‐T constructs currently under exploration in B cell NHL.